Study of protein-CdTe quantum dot interactions. - Wang, Zheng. (2009)
This report presents a systematic study of the interaction mechanism between CdTe quantum dots (QDs) and three typical serum proteins [glucose oxidase (GOD), hemoglobin (Hb) and cytochrome c (Cyt C)] possessing different isoelectric points. The interactions were investigated through two approaches, surface–attached approach and solution–phase approach, using techniques including surface plasmon resonance, atomic force microscopy, hydrodynamic size and zeta potential measurements, and photoluminescence spectrometry. Different binding behaviors of the three proteins and agglomeration of Hb-QD complex can be observed in the experiment results. Electrostatic attraction is proved to be the dominant interaction force of protein-QD associations. Based on the results, surface charge distribution and relative size of the proteins are proposed to be the two main factors determining the protein-QD interactions. This mechanism may also be extended to explain and predict the interaction of proteins and other nanoparticles with electrostatic attraction as the major binding force.